Modeling Normal and Pathological Ear Cartilage in vitro Using Somatic Stem Cells in Three-Dimensional Culture - Zucchelli, Eleonora; Birchall, Martin; Bulstrode, Neil W.; Ferretti, Patrizia (Frontiers in Cell and Developmental Biology, 2020)
Microtia (underdeveloped ear) is a rare congenital dysmorphology affecting the development of the outer ear. Although human microtic cartilage has not been fully characterized, chondrogenic cells derived from this tissue have been proposed as a suitable source for autologous auricular reconstruction. The aim of this study was to further characterize native microtic cartilage and investigate the properties of cartilage stem/progenitor cells (CSPCs) derived from it. Two-dimensional (2D) systems are most commonly used to assess the chondrogenic potential of somatic stem cells in vitro, but limit cell interactions and differentiation. Hence here we investigated the behaviour of microtic CSPCs in three-dimensional spheroid cultures. Remarkable similarities between human microtic cartilages from 5 patients, as compared to normal cartilage, were observed notwithstanding possibly different aetiologies of the disease. Native microtic cartilage displayed poorly defined perichondrium and hyper-cellularity, an immature phenotype that resembled that of the normal developing human auricular cartilage we studied in parallel. Crucially, our analysis of microtic ears revealed for the first time that, unlike normal cartilage, microtic cartilages are vascularized. Importantly, CSPCs isolated from human microtic and normal ear cartilages were found to recapitulate many characteristics of pathological and healthy tissues, respectively, when allowed to differentiate as spheroids, but not in monolayer cultures. Noteworthily, starting from initially homogeneous cell pellets, CSPC spheroids spontaneously underwent a maturation process in culture, and formed two regions (inner and outer region) separated by a boundary, with distinct cell types that differed in chondrogenic commitment as indicated by expression of chondrogenic markers. Compared to normal ear-derived spheroids, microtic spheroids were asymmetric, hyper-cellularised and the inner and outer regions did not develop properly. Hence, their organization resembled that of native microtic cartilage. Together, our results identify novel features of microtic ears and highlight the importance of 3D self-organizing in vitro systems for better understanding somatic stem cell behavior and disease modelling. Our observations of ear-derived chondrogenic stem cell behaviour have implications for choice of cells for tissue engineered reconstructive purposes and for modelling the aetiopathogenesis of microtia.